Conductive paste, rfid inlay, and method for manufacturing rfid inlay
By developing a conductive paste containing alicyclic skeleton polymerizable monomer, the problem of reduced conductivity of RFID inlays under moisture or low temperature conditions is solved, and high conductivity of moisture immersion or low temperature conditions is achieved.
Patent Information
- Application Number
- CN202380059007.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-30
- Filing Date
- 2023-11-29
- Publication Date
- 2025-03-21
AI Technical Summary
The existing RFID inlays tend to lose conductivity under moisture immersion or low temperature conditions, and cannot effectively solve the impact of moisture or low temperature on the connecting structure.
A conductive paste containing a curable compound, a curing agent and a plurality of conductive fillers has been developed. The curable compound contains a polymeric monomer with an alicyclic backbone. Through specific composition and treatment conditions, the water absorption rate of the conductive paste is less than 2.0% when impregnated in water is ensured, thereby maintaining high conductivity reliability.
Even under water immersion or low temperature conditions, the RFID inlay using the conductive paste can maintain high conductivity, solving the impact of moisture and low temperature on the connecting structure.
Smart Images

Figure CN119678226A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste containing a conductive filler, and also to an RFID inlay using the conductive paste and a method for producing the RFID inlay. Background Art
[0002] RFID (Radio Frequency Identification) inlays that can send and receive data in a contactless manner are widely used in contactless RFID tags, contactless RFID cards, etc. In particular, RFID inlays in the UHF (Ultra High Frequency) band (860MHz to 960MHz) have attracted attention due to their long communication distance. RFID inlays in the UHF band are used in various products and applications such as commuter tickets, inventory management, logistics management, and history management.
[0003] In the RFID inlay, a conductive paste containing a conductive filler and a binder resin is used to adhere and connect a chip having electrodes on its surface and a substrate having wiring (antenna pattern) on its surface.
[0004] Patent Document 1 below discloses an adhesive that can be applied to electronic components. The adhesive is an acrylic adhesive composition comprising a free radical initiator having a 10-hour half-life temperature of 80°C or less, an oligomer containing vinylidene, and at least one diluent. The adhesive can be cured quickly at low temperatures, and the adhesive can be used for more than 24 hours at room temperature.
[0005] Patent Document 2 listed below discloses a conductive adhesive comprising a polymerizable acrylic compound, an organic peroxide, and solder particles, wherein the one-minute half-life temperature of the organic peroxide is lower than the solidus temperature of the solder particles.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2006-144018
[0009] Patent Document 2: Japanese Patent Application Publication No. 2013-124330 Summary of the invention
[0010] Technical problem solved by the invention
[0011] As RFID inlays become more common, electronic components such as contactless RFID tags and contactless RFID cards may be attached with moisture such as rain or drinking water. In addition, when electronic components are stored at low temperatures, it is also estimated that condensation may form on the electronic components. Thus, it has been desired to develop a conductive paste that can maintain conduction reliability even when moisture penetrates into electronic components (connection structures).
[0012] An object of the present invention is to provide a conductive paste capable of maintaining high conduction reliability even when moisture enters a connection structure. Another object of the present invention is to provide an RFID inlay using the conductive paste and a method for producing the RFID inlay.
[0013] Technical means of solving problems
[0014] This specification discloses the following conductive paste, RFID inlay, and method for producing the RFID inlay.
[0015] Item 1. A conductive paste comprising a curable compound, a curing agent and a plurality of conductive fillers, wherein:
[0016] The curable compound includes a polymerizable monomer having an alicyclic skeleton,
[0017] When the cured product of the conductive paste was immersed in water for 2 hours at 121° C., 100% RH and 2 atm, the water absorption of the cured product was 2.0% or less.
[0018] Water absorption rate of the cured product (%)=(weight of the cured product after the test-weight of the cured product before the test)×100 / weight of the cured product before the test.
[0019] Item 2. The conductive paste according to Item 1, wherein
[0020] The storage modulus of the cured product before the test is 0.8 GPa or more,
[0021] The storage modulus of the cured product after the test was 0.5 GPa or more.
[0022] Item 3. The conductive paste according to Item 1 or 2, wherein
[0023] A ratio of the storage elastic modulus of the cured product after the test to the storage elastic modulus of the cured product before the test is 0.5 or more.
[0024] Item 4. The conductive paste according to any one of Items 1 to 3, wherein
[0025] The polymerizable monomer having an alicyclic skeleton has a (meth)acryloyl group.
[0026] Item 5. The conductive paste according to any one of Items 1 to 4, wherein
[0027] The polymerizable monomer having an alicyclic skeleton is tricyclodecane dimethanol di(meth)acrylate or isobornyl (meth)acrylate.
[0028] Item 6. The conductive paste according to any one of Items 1 to 5, wherein
[0029] The content of the polymerizable monomer having an alicyclic skeleton in 100% by weight of the curable compound is 10% by weight or more and 50% by weight or less.
[0030] Item 7. The conductive paste according to any one of Items 1 to 6, wherein
[0031] The conductive filler includes nickel.
[0032] Item 8. The conductive paste according to any one of Items 1 to 7, which is used to obtain an RFID inlay.
[0033] Item 9. An RFID inlay comprising:
[0034] A substrate having wiring on its surface,
[0035] A chip having electrodes on its surface, and
[0036] A bonding portion for bonding the substrate and the chip together.
[0037] The material of the bonding portion is the conductive paste described in any one of items 1 to 8,
[0038] The wiring and the electrode are electrically connected via the conductive filler in the bonding portion.
[0039] Item 10. A method for manufacturing an RFID inlay, comprising:
[0040] A first placement step of placing the conductive paste described in any one of items 1 to 8 on a surface of a substrate having wiring on the surface;
[0041] a second placement step of placing a chip having an electrode on a surface of the conductive paste opposite to the substrate side; and
[0042] The bonding step is to heat and pressurize the conductive paste to form a bonding portion where the substrate and the chip are bonded together by the conductive paste, and to electrically connect the wiring and the electrode via the conductive filler in the bonding portion.
[0043] Item 11. A method for manufacturing an RFID inlay according to Item 10, wherein:
[0044] The substrate is in the shape of a long strip.
[0045] In the first arrangement step, the second arrangement step, and the bonding step, the RFID inlay is manufactured by conveying the long substrate by a roll-to-roll method.
[0046] Effects of the Invention
[0047] The conductive paste of the present invention is a conductive paste comprising a curable compound, a curing agent and a plurality of conductive fillers. In the conductive paste of the present invention, the curable compound comprises a polymerizable monomer having an alicyclic skeleton. In the conductive paste of the present invention, when the cured product of the conductive paste is immersed in water for 2 hours under the conditions of 121° C., 100% RH and 2 atm, the water absorption of the cured product is 2.0% or less. In the conductive paste of the present invention, since it has the above-mentioned structure, it is possible to maintain a high conduction reliability even when water penetrates into the connection structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] [ Figure 1 ] Figure 1 This is a cross-sectional view schematically showing an RFID inlay using the conductive paste according to the first embodiment of the present invention. DETAILED DESCRIPTION
[0049] Hereinafter, the present invention is described in detail.
[0050] (Conductive paste)
[0051] The conductive paste of the present invention is a conductive paste comprising a curable compound, a curing agent and a plurality of conductive fillers. In the conductive paste of the present invention, the curable compound comprises a polymerizable monomer having an alicyclic skeleton. In the conductive paste of the present invention, when the cured product of the conductive paste is immersed in water for 2 hours under the conditions of 121° C., 100% RH and 2 atm, the water absorption of the cured product is 2.0% or less.
[0052] Water absorption rate of the cured product (%) = (weight of the cured product after the test - weight of the cured product before the test) × 100 / weight of the cured product before the test
[0053] Since the conductive paste of the present invention has the above-mentioned structure, even when moisture penetrates into the connection structure (electronic component), high conduction reliability can be maintained.
[0054] When the cured product of the conductive paste is immersed in water for 2 hours at 121°C, 100% RH and 2 atm, the water absorption of the cured product is preferably 1.8% or less, more preferably 1.7% or less, further preferably 1.5% or less, particularly preferably 1.0% or less, and most preferably 0.5% or less. When the water absorption of the cured product is below the upper limit, a high conduction reliability can be maintained even when water penetrates into the connection structure (electronic component). The lower limit of the water absorption of the cured product is not particularly limited. The water absorption of the cured product may be 0%, may be above 0%, or may be above 0.1%.
[0055] The water absorption of the solidified product is measured, for example, in the following manner. The conductive paste is heated at 130° C. for 10 minutes to obtain a solidified product (solidified product before the test). The solidified product is immersed in water for 2 hours under the conditions of 121° C., 100% RH and 2 atm to obtain a solidified product after the test. The weight of the solidified product before the test and the weight of the solidified product after the test are measured to calculate the water absorption of the solidified product.
[0056] Water absorption rate of the cured product (%) = (weight of the cured product after the test - weight of the cured product before the test) × 100 / weight of the cured product before the test
[0057] As a method for adjusting the water absorption of the cured product, the following methods can be cited. A method of using the following preferred polymerizable monomers as the polymerizable monomer having an alicyclic skeleton. A method of adjusting the content of the polymerizable monomer having an alicyclic skeleton (particularly, a polymerizable monomer having an alicyclic skeleton and having no polar group).
[0058] The storage modulus of the cured product before the test is preferably 0.8 GPa or more, more preferably 1.0 GPa or more, and more preferably 1.2 GPa or more, and preferably 3.5 GPa or less, more preferably 3.2 GPa or less, and more preferably 3.0 GPa or less. When the storage modulus of the cured product before the test is above the lower limit and below the upper limit, the adhesion and conduction reliability can be further improved.
[0059] The storage modulus of the cured product after the test is preferably 0.3 GPa or more, more preferably 0.4 GPa or more, further preferably 0.5 GPa or more, further preferably 0.8 GPa or more, particularly preferably 1.0 GPa or more, and preferably 3.0 GPa or less, more preferably 2.8 GPa or less, further preferably 2.5 GPa or less. When the storage modulus of the cured product after the test is above the lower limit and below the upper limit, the conduction reliability can be improved, and even when moisture penetrates into the connection structure, high adhesion can be maintained.
[0060] The ratio of the storage modulus of the solidified material after the test to the storage modulus of the solidified material before the test (storage modulus of the solidified material after the test / storage modulus of the solidified material before the test) is preferably 0.3 or more, more preferably 0.5 or more, further preferably 0.6 or more, and particularly preferably 0.7 or more. When the ratio (storage modulus of the solidified material after the test / storage modulus of the solidified material before the test) is above the lower limit, even when moisture penetrates into the connection structure (electronic component), a high conduction reliability can be maintained. The upper limit of the ratio (storage modulus of the solidified material after the test / storage modulus of the solidified material before the test) is not particularly limited. The ratio (storage modulus of the solidified material after the test / storage modulus of the solidified material before the test) can be less than 1.0, can be less than 0.9, and can be less than 0.85.
[0061] As for the storage modulus of the cured product before the test and the storage modulus of the cured product after the test, for example, they are measured in the following manner. The cured product before the test and the cured product after the test are cut into sizes of 10 mm in length, 1 mm to 10 mm in width, and 15 mm to 50 mm in height to prepare measurement samples. For each measurement sample, a dynamic viscoelasticity measuring device (for example, "RSA3" manufactured by TA Instruments) is used to measure the storage modulus of the cured product before the test and the storage modulus of the cured product after the test under the conditions of a frequency of 10 Hz, a strain of 0.1%, a temperature of 20°C to 180°C, and a heating rate of 10°C / min.
[0062] The conductive paste of the present invention is in a paste state at 25° C. The conductive paste is used by being sprayed at, for example, 20° C. to 50° C. The conductive paste of the present invention is preferably used by being sprayed by a spray dispenser.
[0063] The conductive paste has good adhesion, is suitable for use as an adhesive, and is particularly suitable for bonding a substrate to a chip.
[0064] From the viewpoint of further improving the conduction reliability, the conductive paste is preferably an anisotropic conductive paste. The conductive paste is suitable for electrical connection of electrodes. The conductive paste is suitable for use in order to obtain a connection structure. The conductive paste is suitable for use in order to obtain an electronic component. The conductive paste is particularly suitable for use in order to obtain an RFID inlay (the purpose of the conductive paste for obtaining an RFID inlay). The conductive paste is suitable for bonding and connecting a chip having an electrode on its surface to a substrate having wiring (antenna pattern) on its surface (the purpose of the conductive paste for bonding and connecting a chip having an electrode on its surface to a substrate having wiring (antenna pattern) on its surface).
[0065] The conductive paste is preferably used for coating on a substrate having a surface tension of 30 mN / m to 50 mN / m (application of the conductive paste on a substrate having a surface tension of 30 mN / m to 50 mN / m). The conductive paste is preferably used for bonding a substrate having a surface area of 0.50 mm 2 The following chips (for bonding surface area of 0.50mm 2 The following is the use of the conductive paste in the chip).
[0066] The conductive paste is preferably thermosetting, and is more preferably a thermosetting anisotropic conductive paste.
[0067] Hereinafter, each component contained in the conductive paste will be described.
[0068] In the present specification, "(meth)acrylate" means acrylate and methacrylate. "(meth)acrylic" means acrylic and methacrylic. "(meth)acryloyl" means acryloyl and methacryloyl.
[0069] <Curing Compound>
[0070] The curable compound includes a polymerizable monomer having an alicyclic skeleton. The conductive paste has the above structure, so that the water absorption of the cured product can be reduced, and as a result, even when water penetrates into the connection structure (electronic component), high conduction reliability can be maintained.
[0071] The polymerizable monomer having an alicyclic skeleton is preferably a (meth) acrylic compound. The polymerizable monomer having an alicyclic skeleton is preferably a (meth) acryloyl group. The polymerizable monomer having an alicyclic skeleton is preferably a polymerizable monomer having a (meth) acryloyl group. The polymerizable functional group in the polymerizable monomer having an alicyclic skeleton is preferably a (meth) acryloyl group.
[0072] The polymerizable monomer with an alicyclic skeleton preferably does not have a polar group. The polymerizable monomer with an alicyclic skeleton preferably includes a polymerizable monomer with an alicyclic skeleton and no polar group. As the polar group, hydroxyl, amino and carboxyl groups can be cited. In this case, the water absorption of the cured product can be reduced, and as a result, even when water penetrates into the connection structure (electronic component), a high conduction reliability can be maintained.
[0073] The polymerizable monomer having an alicyclic skeleton may be a monofunctional (meth)acrylate or a multifunctional (meth)acrylate. The polymerizable monomer having an alicyclic skeleton may have one (meth)acryloyl group, may have two, may have more than two, and may have less than ten. From the viewpoint of further improving adhesion and conduction reliability and improving ejection properties, the polymerizable monomer having an alicyclic skeleton is preferably a monofunctional (meth)acrylate, preferably having one (meth)acryloyl group.
[0074] Examples of the polymerizable monomer having an alicyclic skeleton include cyclohexyl (meth)acrylate, dimethylol tricyclodecane di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, isobornyl (meth)acrylate, 4-tert-butyl cyclohexanol, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, pentamethylpiperidinyl (meth)acrylate, tetramethylpiperidinyl (meth)acrylate, acryloylmorpholine, and 3,3,5-trimethylcyclohexyl (meth)acrylate. The polymerizable monomer having an alicyclic skeleton may be used alone or in combination of two or more.
[0075] From the viewpoint of maintaining high conduction reliability even when moisture penetrates into the connection structure (electronic component), the polymerizable monomer having an alicyclic skeleton is preferably tricyclodecane dimethanol di(meth)acrylate or isobornyl (meth)acrylate. From the viewpoint of maintaining high conduction reliability even when moisture penetrates into the connection structure (electronic component), the alicyclic skeleton is preferably tricyclodecane alkyl or isobornyl.
[0076] The molecular weight of the polymerizable monomer having an alicyclic skeleton is preferably 50 or more, more preferably 100 or more, further preferably 150 or more, particularly preferably 200 or more, and preferably 1000 or less, more preferably less than 1000, further preferably 900 or less, particularly preferably 800 or less, and most preferably 700 or less. When the molecular weight of the polymerizable monomer having an alicyclic skeleton is within the above range, the viscosity of the conductive paste can be adjusted to a suitable range, the adhesiveness can be further improved, and the conduction reliability can be further improved.
[0077] With respect to the molecular weight of the polymerizable monomer having an alicyclic skeleton, when the structural formula of the polymerizable monomer having an alicyclic skeleton can be determined, it means the molecular weight that can be calculated from the structural formula. In addition, when the structural formula of the polymerizable monomer having an alicyclic skeleton cannot be determined, the molecular weight means the weight average molecular weight. The weight average molecular weight represents the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). The molecular weight of the polymerizable monomer having an alicyclic skeleton is relatively small, so the structural formula can generally be determined. The weight average molecular weight can be measured under the following measuring device and measuring conditions.
[0078] Measurement equipment: "Waters GPC System (Waters 2690 + Waters 2414 (RI))" manufactured by Waters Corporation of Japan
[0079] Column: Shodex GPC LF-G × 1, Shodex GPC LF-804 × 2
[0080] Mobile phase: THF 1.0mL / min
[0081] Sample concentration: 5 mg / mL
[0082] Detector: Differential Refractive Index Detector (RID)
[0083] Standard material: polystyrene (manufactured by TOSOH, weight average molecular weight: 620 to 590,000)
[0084] The curable compound may include curable compounds other than the polymerizable monomer having an alicyclic skeleton. The curable compound other than the polymerizable monomer having an alicyclic skeleton may be a thermosetting compound or a photocurable compound. The curable compound other than the polymerizable monomer having an alicyclic skeleton is preferably a thermosetting compound. The thermosetting compound is a compound that can be cured by heating. As the thermosetting compound, (meth) acrylic compounds, oxetane compounds, epoxy compounds, episulfide compounds, phenol compounds, amino compounds, unsaturated polyester compounds, polyurethane compounds, polysiloxane compounds and polyimide compounds can be cited. The curable compound other than the polymerizable monomer having an alicyclic skeleton may be used alone or in combination of two or more.
[0085] From the viewpoint of further improving adhesion and conduction reliability and improving ejection properties, the curable compound other than the polymerizable monomer having an alicyclic skeleton preferably includes an epoxy compound or a (meth) acrylic compound, and more preferably includes a (meth) acrylic compound. From the viewpoint of improving adhesion, the curable compound other than the polymerizable monomer having an alicyclic skeleton more preferably includes a compound having a (meth) acryloyl group ((meth) acrylate).
[0086] From the viewpoint of maintaining a high conduction reliability even when moisture penetrates into the connection structure (electronic component), the curable compound other than the polymerizable monomer having an alicyclic skeleton preferably has two or more (meth)acryloyl groups. The curable compound other than the polymerizable monomer having an alicyclic skeleton is preferably a multifunctional (meth)acrylate. The multifunctional (meth)acrylate may be a difunctional (meth)acrylate, a trifunctional (meth)acrylate, or a tetrafunctional or higher (meth)acrylate. The curable compound other than the polymerizable monomer having an alicyclic skeleton may have two (meth)acryloyl groups, may have two or more, may have three or more, may have four or more, and may have ten or less.
[0087] Examples of the polyfunctional (meth)acrylate include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol (meth)acrylate, 1,9-nonanediol di(meth)acrylate, polyethylene glycol (200) di(meth)acrylate, tetraethylene glycol di(meth)acrylate, triethylene glycol (meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol (400) di(meth)acrylate, dipropylene glycol di(meth)acrylate, alkoxylated hexanediol di(meth)acrylate, and dodecanediol di(meth)acrylate. (meth)acrylate, polyethylene glycol (600) di(meth)acrylate, polypropylene glycol (700) (meth)acrylate, propoxylated (2) neopentyl glycol di(meth)acrylate, alkoxylated neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, Tris-(2-hydroxyethyl)isocyanurate tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated (3) trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate and dipentaerythritol hexa(meth)acrylate, etc.
[0088] From the viewpoint of further improving the adhesiveness and conduction reliability and improving the ejection property, the curable compound other than the polymerizable monomer having an alicyclic skeleton preferably contains urethane (meth)acrylate.
[0089] The molecular weight of the urethane (meth) acrylate is preferably 1000 or more, more preferably 1500 or more, further preferably 2000 or more, further preferably 3000 or more, particularly preferably 5000 or more, and preferably 30000 or less, more preferably 25000 or less, further preferably 20000 or less, and particularly preferably 18000 or less. When the molecular weight of the urethane (meth) acrylate is above the lower limit and below the upper limit, the adhesiveness can be further improved, and the conduction reliability can be further improved.
[0090] With respect to the molecular weight of the carbamate (meth) acrylate, when the structural formula of the carbamate (meth) acrylate can be determined, it means the molecular weight that can be calculated from the structural formula. In addition, when the structural formula of the carbamate (meth) acrylate cannot be determined, the molecular weight means the weight average molecular weight. The weight average molecular weight represents the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). The molecular weight of the carbamate (meth) acrylate is preferably the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). The weight average molecular weight can be measured under the following measuring device and measuring conditions.
[0091] Measurement equipment: "Waters GPC System (Waters 2690 + Waters 2414 (RI))" manufactured by Waters Corporation of Japan
[0092] Column: Shodex GPC LF-G × 1, Shodex GPC LF-804 × 2
[0093] Mobile phase: THF 1.0mL / min
[0094] Sample concentration: 5 mg / mL
[0095] Detector: Differential Refractive Index Detector (RID)
[0096] Standard material: polystyrene (manufactured by TOSOH, weight average molecular weight: 620 to 590,000)
[0097] In 100 wt % of the conductive paste, the content of the curable compound is preferably 30 wt % or more, more preferably 50 wt % or more, and preferably 90 wt % or less, more preferably 85 wt % or less, and further preferably 80 wt % or less. When the content of the curable compound is above the lower limit and below the upper limit, the adhesiveness can be further improved, and the conduction reliability can be further improved.
[0098] In 100 wt % of the conductive paste, the content of the polymerizable monomer having an alicyclic skeleton is preferably 5 wt % or more, more preferably 15 wt % or more, and preferably 50 wt % or less, more preferably 45 wt % or less, further preferably 40 wt % or less, and particularly preferably 35 wt % or less. When the content of the polymerizable monomer having an alicyclic skeleton is above the lower limit and below the upper limit, even when moisture penetrates into the connection structure (electronic component), a high conduction reliability can be maintained. When two or more polymerizable monomers having an alicyclic skeleton are used in combination, the content of the polymerizable monomer having an alicyclic skeleton represents the total content of the polymerizable monomers having an alicyclic skeleton.
[0099] In 100% by weight of the curable compound, the content of the polymerizable monomer having an alicyclic skeleton is preferably 5% by weight or more, more preferably 10% by weight or more, further preferably 20% by weight or more, and preferably 50% by weight or less, more preferably 40% by weight or less, and further preferably 30% by weight or less. When the content of the polymerizable monomer having an alicyclic skeleton is above the lower limit and below the upper limit, even when moisture penetrates into the connection structure (electronic component), a high conduction reliability can be maintained. In the case where two or more polymerizable monomers having an alicyclic skeleton are used in combination, the content of the polymerizable monomer having an alicyclic skeleton represents the total content of the polymerizable monomer having an alicyclic skeleton.
[0100] In 100 wt % of the curable compound, the content of the urethane (meth) acrylate is preferably 15 wt % or more, more preferably 20 wt % or more, and preferably 50 wt % or less, more preferably 45 wt % or less. When the content of the urethane (meth) acrylate is above the lower limit and below the upper limit, the adhesion can be improved and the conduction reliability can be further improved.
[0101] In 100 wt % of the curable compound, the total content of the polymerizable monomer having an alicyclic skeleton and the urethane (meth) acrylate is preferably 20 wt % or more, more preferably 40 wt % or more, and preferably 95 wt % or less, more preferably 90 wt % or less. When the total content of the polymerizable monomer having an alicyclic skeleton and the urethane (meth) acrylate is above the lower limit and below the upper limit, even when moisture penetrates into the connection structure (electronic component), high conduction reliability can be maintained.
[0102] In the total 100 wt % of the polymerizable monomer having an alicyclic skeleton and the urethane (meth) acrylate, the content of the polymerizable monomer having an alicyclic skeleton is preferably 15 wt % or more, more preferably 20 wt % or more, and preferably 80 wt % or less, more preferably 70 wt % or less. When the content of the polymerizable monomer having an alicyclic skeleton is above the lower limit and below the upper limit, even when moisture penetrates into the connection structure (electronic component), high conduction reliability can be maintained.
[0103] In the polymerizable monomer with an alicyclic skeleton of 100% by weight, the content of the polymerizable monomer with an alicyclic skeleton and without a polar group is preferably 50% by weight or less, more preferably 45% by weight or less, and further preferably 40% by weight or less. When the content of the polymerizable monomer with an alicyclic skeleton and without a polar group is below the upper limit, the water absorption rate of the cured product can be reduced. As a result, even when moisture penetrates into the connection structure (electronic component), a high conduction reliability can be maintained. In the polymerizable monomer with an alicyclic skeleton of 100% by weight, the lower limit of the content of the polymerizable monomer with an alicyclic skeleton and without a polar group is not particularly limited. In the polymerizable monomer with an alicyclic skeleton of 100% by weight, the content of the polymerizable monomer with an alicyclic skeleton and without a polar group can be 5% by weight or more, and can be 10% by weight or more.
[0104] <Conductive filler>
[0105] The conductive paste contains a plurality of conductive fillers. The conductive filler is not particularly limited. The conductive filler may be conductive particles or carbon fibers. It should be noted that, in this specification, "containing a plurality of conductive fillers" means that the conductive paste contains more than two conductive fillers. The conductive filler may be used alone or in combination of two or more.
[0106] The shape of the conductive filler is not particularly limited, and the conductive filler may be spherical, may be a shape other than a spherical shape, may be flat, and the like.
[0107] The conductive filler is preferably a conductive particle. The conductive particle may be a solder particle or a metal particle. The metal particle may be a metal powder. The conductive particle may include a substrate particle and a conductive portion disposed on the surface of the substrate particle. From the viewpoint of further improving conduction reliability, the conductive particle preferably includes a substrate particle and a conductive portion disposed on the surface of the substrate particle.
[0108] The particle size of the conductive particles is preferably 0.1 μm or more, more preferably 1 μm or more, and further preferably 3 μm or more, and is preferably 100 μm or less, more preferably 30 μm or less, and further preferably 10 μm or less. When the particle size of the conductive particles is above the lower limit and below the upper limit, the conduction reliability can be further improved.
[0109] The particle size of the conductive particles is preferably an average particle size, more preferably a number average particle size. The average particle size of the conductive particles can be determined, for example, by observing 50 random conductive particles under an electron microscope or an optical microscope and calculating the average value of the particle size of each conductive particle, or by performing laser diffraction particle size distribution measurement.
[0110] In the conductive particles, when the particle size of the conductive particles is measured by observing 50 arbitrary conductive particles under an electron microscope or an optical microscope, for example, it can be measured in the following manner. Add to "TECHNOVIT4000" manufactured by Kulzer Company in a manner such that the content of the conductive particles is 30% by weight, disperse it, and prepare an embedded resin body for conductive particle inspection. Use an ion milling device ("IM4000" manufactured by HITACHI HIGH-TECHNOLOGIES) in a manner such that it passes through the center of the conductive particles dispersed in the embedded resin body for conductive particle inspection, and cut out the cross section of the conductive particles. In addition, using a field emission scanning electron microscope (FE-SEM), set the image magnification to 25,000 times, randomly select 50 conductive particles, and observe each conductive particle. Measure the circle equivalent diameter of each conductive particle, and take the arithmetic average as the particle size of the conductive particle.
[0111] The coefficient of variation (CV value) of the particle size of the conductive particles is preferably 10% or less, more preferably 5% or less. When the coefficient of variation of the particle size of the conductive particles is below the upper limit, the conduction reliability can be further improved. The lower limit of the coefficient of variation (CV value) of the particle size of the conductive particles is not particularly limited. The coefficient of variation (CV value) of the particle size of the conductive particles may be 0% or more, and may be 1% or more.
[0112] The coefficient of variation (CV value) can be measured in the following manner.
[0113] CV value (%) = (ρ / Dn) × 100
[0114] ρ: Standard deviation of particle size of conductive particles
[0115] Dn: average value of particle size of conductive particles
[0116] In 100 wt % of the conductive paste, the content of the conductive filler is preferably 0.01 wt % or more, more preferably 0.1 wt % or more, and preferably 80 wt % or less, more preferably 60 wt % or less, further preferably 40 wt % or less, particularly preferably 20 wt % or less, and most preferably 10 wt % or less. When the content of the conductive filler is above the lower limit and below the upper limit, the conduction reliability can be further improved.
[0117] The content of the conductive filler is preferably 2 parts by weight or more, more preferably 3 parts by weight or more, further preferably 5 parts by weight or more, and particularly preferably 7 parts by weight or more, relative to 100 parts by weight of the curable compound in the conductive paste. The content of the conductive filler is preferably 35 parts by weight or less, more preferably 30 parts by weight or less, further preferably 25 parts by weight or less, and particularly preferably 20 parts by weight or less, relative to 100 parts by weight of the curable compound in the conductive paste. When the content of the conductive filler in the conductive paste is above the lower limit and below the upper limit, the conduction reliability can be further improved.
[0118] The conductive filler preferably contains a metal. Examples of the metal include gold, silver, copper, platinum, palladium, zinc, lead, aluminum, cobalt, indium, ruthenium, nickel, chromium, titanium, antimony, bismuth, germanium, and cadmium, as well as alloys thereof. In addition, tin-doped indium oxide (ITO) can be used as the metal. The metal may be used alone or in combination of two or more.
[0119] From the viewpoint of further reducing the connection resistance between electrodes, the conductive filler preferably includes: an alloy containing tin, nickel, palladium, ruthenium, silver, copper or gold, and more preferably includes nickel or palladium. From the viewpoint of improving the corrosion resistance of the conductive filler and maintaining high conduction reliability, the conductive filler preferably includes nickel or gold, and more preferably includes nickel. From the viewpoint of improving the corrosion resistance of the conductive filler and maintaining high conduction reliability, the conductive filler particularly preferably includes nickel on the outer surface.
[0120] When the conductive particles are metal particles, the metal of the material of the metal particles includes silver, copper, nickel, silicon, gold, titanium, and alloys such as solder. From the viewpoint of further effectively improving the conduction reliability, the material of the metal particles preferably includes nickel or a nickel alloy, and the material of the metal particles is more preferably nickel or a nickel alloy. From the viewpoint of further effectively improving the conduction reliability, the outer surface portion of the metal particles preferably includes nickel or a nickel alloy.
[0121] Hereinafter, the electroconductive particle provided with the substrate particle and the electroconductive part arrange|positioned on the surface of the said substrate particle is demonstrated in detail.
[0122] (Base material particles)
[0123] As the substrate particles, resin particles, inorganic particles other than metal particles, organic-inorganic hybrid particles and metal particles can be cited. The substrate particles are preferably substrate particles other than metal particles, more preferably resin particles, inorganic particles other than metal particles or organic-inorganic hybrid particles. The substrate particles can be core-shell particles having a core and a shell disposed on the surface of the core. The core can be an organic core, and the shell can be an inorganic shell.
[0124] The substrate particles are more preferably resin particles or organic-inorganic hybrid particles, and may be resin particles or organic-inorganic hybrid particles. By using these preferred substrate particles, the effects of the present invention can be more effectively exerted.
[0125] As the material of the resin particles, various resins can be suitably used. As the material of the resin particles, polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene can be cited; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polyalkylene terephthalate, polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenolic resin, melamine resin, benzoguanamine resin, urea formaldehyde resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polysulfone, polyphenylene ether, polyacetal, polyimide, polyamideimide, polyetheretherketone, polyethersulfone, divinylbenzene polymer, and polymers obtained by polymerizing one or more polymerizable monomers having ethylenically unsaturated groups, etc. The divinylbenzene polymer can be a divinylbenzene copolymer. Examples of the divinylbenzene-based copolymer include divinylbenzene-styrene copolymers and divinylbenzene-(meth)acrylate copolymers.
[0126] From the perspective of being able to design and synthesize resin particles having arbitrary compression characteristics suitable for the conductive paste and easily controlling the hardness of the resin particles within an appropriate range, the material of the resin particles is preferably a polymer obtained by polymerizing one or more polymerizable monomers having multiple ethylenically unsaturated groups.
[0127] When the resin particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, examples of the polymerizable monomer having an ethylenically unsaturated group include non-crosslinking monomers and crosslinking monomers.
[0128] Examples of the non-crosslinking monomer include styrene monomers such as styrene and α-methylstyrene; carboxyl monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; and alkyl (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. substances; (meth)acrylate compounds containing oxygen atoms such as 2-hydroxyethyl (meth)acrylate, glyceryl (meth)acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; vinyl acetate, vinyl butyrate, vinyl laurate, vinyl stearate and other acid vinyl ester compounds; unsaturated hydrocarbons such as ethylene, propylene, isoprene, and butadiene; halogen-containing monomers such as trifluoromethyl (meth)acrylate, pentafluoroethyl (meth)acrylate, vinyl chloride, vinyl fluoride, and chlorostyrene, etc.
[0129] Examples of the crosslinking monomer include polyfunctional (meth)acrylate compounds such as tetramethylolmethane tetra(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, (poly)tetramethylene glycol di(meth)acrylate, and 1,4-butanediol di(meth)acrylate; and silane-containing monomers such as triallyl (iso)cyanurate, triallyl trimellitate, divinylbenzene, diallyl phthalate, diallyl acrylamide, diallyl ether, γ-(meth)acryloxypropyltrimethoxysilane, trimethoxysilylstyrene, and vinyltrimethoxysilane.
[0130] The resin particles can be obtained by polymerizing the polymerizable monomer having an ethylenically unsaturated group by a known method, such as a suspension polymerization method in the presence of a free radical polymerization initiator, and a method of using non-crosslinked seed particles to swell the free radical polymerization initiator and the monomer to polymerize.
[0131] When the substrate particles are inorganic particles other than metal particles or organic-inorganic hybrid particles, the inorganic material of the substrate particles includes silicon dioxide, aluminum oxide, barium titanate, zirconium oxide, and carbon black. The inorganic material is preferably not a metal. The particles formed by the silicon dioxide are not particularly limited, and for example, particles obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form cross-linked polymer particles and then firing as required can be cited. As the organic-inorganic hybrid particles, for example, organic-inorganic hybrid particles obtained by cross-linking an alkoxysilyl polymer and an acrylic resin can be cited.
[0132] The organic-inorganic hybrid particles are preferably core-shell organic-inorganic hybrid particles having a core and a shell disposed on the surface of the core. The core is preferably an organic core. The shell is preferably an inorganic shell. From the viewpoint of further effectively reducing the connection resistance between electrodes, the substrate particles are preferably organic-inorganic hybrid particles having an organic core and an inorganic shell disposed on the surface of the organic core.
[0133] Examples of the material of the organic core include the material of the resin particles described above.
[0134] As the material of the inorganic shell, the inorganic substances mentioned as the material of the substrate particles can be cited. The material of the inorganic shell is preferably silicon dioxide. The inorganic shell is preferably formed by firing the shell after metal alkoxide is made into a shell-like object by a sol-gel method on the surface of the core. The metal alkoxide is preferably a silane alkoxide. The inorganic shell is preferably formed by a silane alkoxide.
[0135] When the substrate particles are metal particles, examples of the metal used as the material of the metal particles include silver, copper, nickel, silicon, gold, titanium, and alloys such as solder.
[0136] The particle size of the substrate particles is preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.5 μm or more, further preferably 1 μm or more, particularly preferably 3 μm or more, and preferably 50 μm or less, more preferably 30 μm or less, further preferably 20 μm or less, and particularly preferably 10 μm or less. When the particle size of the substrate particles is above the lower limit, the conduction reliability becomes higher. In addition, when the conductive portion is formed on the surface of the substrate particles, it becomes difficult to condense, and it becomes difficult to form condensed conductive particles. When the particle size of the substrate particles is below the upper limit, the conductive particles are easily fully compressed, and the connection resistance between the electrodes connected by the conductive particles can be further effectively reduced.
[0137] The particle size of the substrate particles is preferably an average particle size, more preferably a number average particle size. The number average particle size of the substrate particles can be measured, for example, in the following manner. In such a way that the content of the conductive particles is 30% by weight, it is added to "TECHNOVIT4000" manufactured by Kulzer Company, dispersed, and an embedded resin body for substrate particle inspection is prepared. An ion milling device (HITACHI HIGH-TECHNOLOGIES "IM4000") is used to cut out the cross section of the conductive particles in the conductive particles embedded in the resin body dispersed to the substrate particles to be inspected. In addition, using a field emission scanning electron microscope (FE-SEM), the image magnification is set to 25,000 times, 50 conductive particles are randomly selected, and the substrate particles of each conductive particle are observed. The particle size of the substrate particles in each conductive particle is measured, and the arithmetic average is taken as the average particle size of the substrate particles.
[0138] (Conductive part)
[0139] The conductive portion preferably comprises a metal. The metal constituting the conductive portion is not particularly limited. As the metal, for example, gold, silver, copper, platinum, palladium, zinc, lead, aluminum, cobalt, indium, ruthenium, nickel, chromium, titanium, antimony, bismuth, germanium and cadmium, and alloys thereof, etc. can be cited. In addition, as the metal, tin-doped indium oxide (ITO) can be used. The metal can be used only one or in combination of two or more. From the viewpoint of further reducing the connection resistance between the electrodes, it is preferably an alloy containing tin, nickel, palladium, ruthenium, silver, copper or gold, and more preferably nickel or palladium.
[0140] From the viewpoint of further effectively improving conduction reliability, the conductive portion preferably includes nickel, and more preferably the outer surface portion of the conductive portion includes nickel.
[0141] The content of nickel in 100 wt % of the conductive portion containing nickel is preferably 10 wt % or more, more preferably 50 wt % or more, further preferably 60 wt % or more, further preferably 70 wt % or more, and particularly preferably 90 wt % or more. The content of nickel in 100 wt % of the conductive portion containing nickel may be 99 wt % or less, 90 wt % or less, or 70 wt % or less.
[0142] The conductive portion may be formed from a single layer. The conductive portion may be formed from multiple layers. That is, the conductive portion may have a laminated structure of more than two layers. When the conductive portion is formed from multiple layers, the metal constituting the outermost layer is preferably gold, silver, nickel, palladium, ruthenium, copper or an alloy containing tin, more preferably nickel. When the metal constituting the outermost layer is one of these preferred metals, the connection resistance between the electrodes becomes further lower.
[0143] The method for forming the conductive portion on the surface of the substrate particles is not particularly limited. As the method for forming the conductive portion, for example, a method based on electroless plating, a method based on electroplating, a method based on physical collision, a method based on a mechanochemical reaction, a method based on physical evaporation or physical adsorption, and a method of applying a paste comprising metal powder or metal powder and an adhesive to the surface of substrate particles, etc. can be cited. The method for forming the conductive portion is preferably a method based on electroless plating, electroplating or physical collision. As the method based on physical evaporation, methods such as vacuum evaporation, ion plating and ion sputtering can be cited. In addition, in the method based on physical collision, for example, THETACOMPOSER (TOKUJU company system) is used.
[0144] The thickness of the conductive portion is preferably 0.005 μm or more, more preferably 0.01 μm or more, preferably 10 μm or less, more preferably 1 μm or less, and further preferably 0.3 μm or less. When the thickness of the conductive portion is above the lower limit and below the upper limit, sufficient conductivity can be obtained, and the conductive particles will not become too hard, and the conductive particles can be sufficiently deformed during connection.
[0145] When the conductive portion is formed of multiple layers, the thickness of the conductive portion of the outermost layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, preferably 0.5 μm or less, and more preferably 0.1 μm or less. When the thickness of the conductive portion of the outermost layer is above the lower limit and below the upper limit, the conductive portion of the outermost layer becomes uniform, the corrosion resistance becomes sufficiently high, and the connection resistance between the electrodes can be sufficiently reduced.
[0146] The thickness of the conductive portion can be measured, for example, by observing a cross section of the conductive particle using a transmission electron microscope (TEM).
[0147] Core material:
[0148] The conductive particles preferably have a plurality of protrusions on the outer surface of the conductive portion. An oxide film is often formed on the surface of the electrode connected by the conductive particles. When conductive particles having protrusions on the surface of the conductive portion are used, the oxide film can be effectively removed by arranging the conductive particles between the electrodes and pressing them. Therefore, the electrode and the conductive portion are further reliably in contact, and the connection resistance between the electrodes is further reduced. In addition, when connecting between the electrodes, the filler between the conductive particles and the electrode can be effectively removed by the protrusions of the conductive particles. Therefore, the conduction reliability between the electrodes becomes higher.
[0149] As a method for forming the protrusion, there can be cited a method of forming a conductive portion by electroless plating after attaching a core material to the surface of a substrate particle; and a method of forming a conductive portion by electroless plating on the surface of a substrate particle, attaching a core material, and further forming a conductive portion by electroless plating, etc. In addition, in order to form the protrusion, the following method can also be used: without using the core material, after the substrate particle forms a conductive portion by electroless plating, a plating layer is precipitated in a protrusion shape on the surface of the conductive portion, and a conductive portion is further formed by electroless plating, etc.
[0150] As a method for attaching a core material to the surface of a substrate particle, for example, a method of adding a core material to a dispersion of substrate particles, a method of aggregating and attaching the core material to the surface of the substrate particles by van der Waals force, and a method of adding a core material to a container to which substrate particles are added, and attaching the core material to the surface of the substrate particles by mechanical action based on the rotation of the container, etc. From the viewpoint of controlling the amount of the attached core material, the method of attaching the core material to the surface of the substrate particles is preferably a method of aggregating and attaching the core material to the surface of the substrate particles in the dispersion.
[0151] As the material constituting the core material, conductive materials and non-conductive materials can be cited. As the conductive material, for example, conductive non-metals such as metals, metal oxides, graphite, and conductive polymers can be cited. As the conductive polymer, polyacetylene can be cited. As the non-conductive material, silicon dioxide, aluminum oxide, titanium oxide, tungsten carbide, zirconium oxide, etc. can be cited. From the viewpoint of further improving the conduction reliability between electrodes, the core material is preferably a metal.
[0152] The metal is not particularly limited. As the metal, for example, metals such as gold, silver, copper, platinum, zinc, iron, lead, tin, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium and cadmium, and alloys consisting of two or more metals such as tin-lead alloy, tin-copper alloy, tin-silver alloy, tin-lead-silver alloy and tungsten carbide can be cited. From the viewpoint of further improving the conduction reliability between electrodes, the metal is preferably nickel, copper, silver or gold. The metal may be the same as or different from the metal constituting the conductive portion.
[0153] The shape of the core material is not particularly limited. The shape of the core material is preferably a block. Examples of the core material include a particle-shaped block, an aggregated block of a plurality of fine particles, and an indefinite-shaped block.
[0154] The particle size (average particle size) of the core material is preferably 0.001 μm or more, more preferably 0.05 μm or more, preferably 0.9 μm or less, more preferably 0.2 μm or less. When the particle size of the core material is above the lower limit and below the upper limit, the connection resistance between electrodes can be effectively reduced.
[0155] The particle size of the core material is preferably an average particle size, more preferably a number average particle size. The particle size of the core material can be determined, for example, by observing 50 arbitrary core materials under an electron microscope or an optical microscope and calculating the average particle size of each core material; or by performing a laser diffraction particle size distribution measurement.
[0156] <Curing Agent>
[0157] From the viewpoint of curing the curable compound containing the polymerizable monomer having an alicyclic skeleton, the curing agent is preferably a polymerization initiator. Examples of the polymerization initiator include photopolymerization initiators and thermal polymerization initiators. The polymerization initiator may be used alone or in combination of two or more.
[0158] From the viewpoint of curing the curable compound by heating, the polymerization initiator preferably includes a thermal polymerization initiator. The thermal polymerization initiator preferably includes a thermal free radical polymerization initiator, preferably a thermal free radical polymerization initiator. Examples of the thermal free radical polymerization initiator include peroxide-based free radical polymerization initiators, azo-based free radical polymerization initiators, and redox-based free radical polymerization initiators.
[0159] Examples of the azo radical polymerization initiator include azobisisobutyronitrile, azobiscyclohexanecarbonitrile, and azobisdimethylvaleronitrile.
[0160] As the peroxide free radical polymerization initiator, diacyl free radical polymerization initiator, peroxyester free radical polymerization initiator, dialkyl free radical polymerization initiator, percarbonate free radical polymerization initiator and ketone peroxide free radical polymerization initiator etc. can be mentioned. As the diacyl free radical polymerization initiator, lauroyl peroxide and benzoyl peroxide etc. can be mentioned. As the peroxyester free radical polymerization initiator, tert-butyl perbenzoate, tert-butyl peracetate, tert-butyl peroxypivalate and tert-butyl peroxy-2-ethylhexanoate etc. can be mentioned. As the dialkyl free radical polymerization initiator, diisopropyl peroxide and di-tert-butyl peroxide etc. can be mentioned. As the percarbonate free radical polymerization initiator, diisopropyl peroxydicarbonate etc. can be mentioned. As the ketone peroxide free radical polymerization initiator, methyl ethyl ketone peroxide etc. can be mentioned.
[0161] The redox free radical polymerization initiator comprises, for example, a peroxide and a reducing agent or a metal-containing compound. Specific examples of the redox free radical polymerization initiator include a mixture of benzoyl peroxide and an organic amine, a mixture of the peroxyester free radical polymerization initiator and a reducing agent such as a thiol, and a mixture of methyl ethyl ketone peroxide and an organic cobalt salt.
[0162] From the viewpoint of improving reactivity and storage stability, the polymerization initiator preferably contains a peroxide-based radical polymerization initiator.
[0163] From the viewpoint of improving reactivity and storage stability, the content of the curing agent (polymerization initiator) in 100 wt % of the conductive paste is preferably 0.1 wt % or more, more preferably 0.3 wt % or more, further preferably 0.5 wt % or more, and is preferably 5 wt % or less, more preferably 4 wt % or less, further preferably 3 wt % or less.
[0164] The content of the curing agent (polymerization initiator) is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and further preferably 0.7 parts by weight or more, and is preferably 6 parts by weight or less, more preferably 5 parts by weight or less, and further preferably 4 parts by weight or less, relative to 100 parts by weight of the curable compound in the conductive paste. When the content of the curing agent (polymerization initiator) is above the lower limit and below the upper limit, reactivity and storage stability can be improved.
[0165] <Other ingredients>
[0166] The conductive paste may contain ingredients other than the curable compound, the curing agent, and the plurality of conductive fillers. As for the conductive paste, other ingredients may include solvents, inorganic fillers, organic fillers, colorants, polymerization inhibitors, chain transfer agents, antioxidants, ultraviolet absorbers, defoamers, leveling agents, surfactants, slip agents, antiblocking agents, waxes, masking agents, deodorants, fragrances, preservatives, antibacterial agents, antistatic agents, and adhesion-imparting agents.
[0167] (RFID inlay and method for manufacturing the RFID inlay)
[0168] The RFID inlay of the present invention comprises a substrate having wiring on its surface,
[0169] A chip having an electrode on its surface, and a bonding portion for bonding the substrate and the chip. In the RFID inlay of the present invention, the material of the bonding portion is the conductive paste. In the RFID inlay of the present invention, the wiring and the electrode are electrically connected through the conductive filler in the bonding portion.
[0170] Figure 1 This is a cross-sectional view schematically showing an RFID inlay using the conductive paste according to the first embodiment of the present invention.
[0171] Figure 1 The RFID inlay 81 shown has a substrate 82 with wiring on the surface, a chip 83 with electrodes on the surface, and a bonding portion 84 that bonds the substrate 82 and the chip 83. The material of the bonding portion 84 is a conductive paste containing a conductive filler 1. The bonding portion 84 is formed by the conductive paste containing the conductive filler 1. The bonding portion 84 is preferably formed by curing the conductive paste containing the conductive filler 1.
[0172] The substrate 82 has wiring 82 a on the surface (upper surface). The chip 83 has electrodes 83 a on the surface (lower surface). The wiring 82 a and the electrode 83 a are electrically connected via the conductive filler 1 in the bonding portion 84 .
[0173] The manufacturing method of the RFID inlay of the present invention comprises the following steps (1) to (3). (1) A first configuration step, which configures the conductive paste on the surface of a substrate having wiring on the surface. (2) A second configuration step, which configures a chip having electrodes on the surface of the conductive paste opposite to the substrate. (3) A bonding step, which heats and pressurizes the conductive paste to form a bonding portion that bonds the substrate and the chip, and electrically connects the wiring and the electrode through the conductive filler in the bonding portion.
[0174] In the RFID inlay and the method for manufacturing the RFID inlay of the present invention, since a specific conductive paste is used, the adhesion between the substrate and the chip can be improved, and the conduction reliability can be improved.
[0175] In the manufacturing method of the RFID inlay, the substrate is preferably in a long strip shape, and in the first configuration step, the second configuration step, and the bonding step, the long strip substrate is conveyed in a roll-to-roll manner to manufacture the RFID inlay. In this case, a plurality of RFID inlays can be manufactured continuously, which can further improve the manufacturing efficiency of the RFID inlay.
[0176] When a roll-to-roll method is used, the conveyance speed of the substrate is not particularly limited.
[0177] Examples of a method for disposing the conductive paste include coating with a dispenser, screen printing, and discharge with an inkjet device.
[0178] The heating temperature in the bonding step is preferably 100° C. or higher, more preferably 150° C. or higher, and preferably 400° C. or lower, more preferably 300° C. or lower, and further preferably 250° C. or lower. When the heating temperature in the bonding step is above the lower limit and below the upper limit, the electrical connection between the chip and the wiring (antenna pattern) can be improved.
[0179] The pressurizing pressure in the bonding step is preferably 0.5 N or more, more preferably 1 N or more, and preferably 3.5 N or less, more preferably 3 N or less, and further preferably 2.5 N or less. When the pressurizing pressure in the bonding step is above the lower limit and below the upper limit, the adhesion between the substrate and the chip can be improved, and the conduction reliability can be improved.
[0180] The heating and pressurizing time in the bonding step is not particularly limited, and may be 2 seconds or longer, 15 seconds or shorter, or 10 seconds or shorter.
[0181] The RFID inlay can be cut into a given size as needed, or it can be cut for use. Preferably, on the long strip substrate, the plurality of chips are bonded by the plurality of bonding portions. On the long strip substrate, a stack of the plurality of chips and the bonding portions can be arranged. In the first arrangement step, the conductive paste is preferably arranged at a plurality of positions on the surface of the long strip substrate. In the second arrangement step, a plurality of chips are preferably used, and the chips are arranged on the surface opposite to the substrate side of each of the conductive pastes arranged at a plurality of positions. After the chips are bonded to the long strip substrate by the bonding portions, the long strip substrate can be cut.
[0182] The substrate is not particularly limited. The substrate is preferably a circuit substrate. Examples of the circuit substrate include resin films, flexible printed substrates, rigid flexible substrates, glass substrates, and paper substrates. The substrate may be a resin substrate, a glass substrate, or a paper substrate.
[0183] The substrate has wiring (antenna pattern) on the surface. The substrate has wiring (antenna pattern) formed on the surface. The substrate preferably has a base material and wiring (antenna pattern) arranged on the surface of the base material.
[0184] As the material of the substrate, resin, glass, paper, etc. can be cited. As the resin, PET (polyethylene terephthalate), PP (polypropylene), PVC (polyvinyl chloride), etc. can be cited. As for the paper, it can be impregnated with epoxy resin or phenolic resin. From the viewpoint of further improving the adhesiveness and the viewpoint of manufacturing the RFID inlay by a roll-to-roll method, the material of the substrate is preferably resin or paper, and more preferably PET (polyethylene terephthalate) or paper. The substrate can be resin, glass, or paper.
[0185] Examples of the wiring (antenna pattern) include gold wiring, nickel wiring, tin wiring, aluminum wiring, silver wiring, SUS wiring, copper wiring, molybdenum wiring, and tungsten wiring. From the viewpoint of improving the operating sensitivity in the UHF band (860 MHz to 920 MHz), the wiring is preferably aluminum wiring.
[0186] From the viewpoint of suppressing thermal deformation of the substrate when mounting a chip (eg, IC chip) and improving flexibility, the thickness of the substrate is preferably 20 μm or more, more preferably 30 μm or more, preferably 200 μm or less, more preferably 100 μm or less.
[0187] The shapes of the substrate and the base material are not particularly limited. From the perspective of manufacturing the RFID inlay by a roll-to-roll method, the substrate and the base material are preferably in a long strip shape. The length of the substrate and the base material is not particularly limited. The length of the substrate and the base material may be greater than 1 m, greater than 10 m, less than 5000 m, or less than 1000 m.
[0188] The surface tension of the substrate (base material) is preferably 30 mN / m or more, more preferably 32 mN / m or more, and further preferably 34 mN / m or more, and is preferably 50 mN / m or less, more preferably 48 mN / m or less, and further preferably 45 mN / m or less. When the surface tension of the substrate (base material) is above the lower limit and below the upper limit, the adhesiveness can be further improved. The conductive paste of the present invention can be suitably used for coating on a substrate (base material) having a surface tension above the lower limit and below the upper limit.
[0189] The surface tension of the substrate (base material) can be measured by the following method based on JIS K6768. A cotton swab is soaked with a JIS specified liquid and applied to the substrate (base material). The surface tension is determined from the shape of the coating film 2 seconds after the application.
[0190] Examples of the chip include semiconductor chips (IC chips) and the like.
[0191] The chip has an electrode on the surface. As the electrode, metal electrodes such as a gold electrode, a nickel electrode, a tin electrode, an aluminum electrode, a silver electrode, a SUS electrode, a copper electrode, a molybdenum electrode and a tungsten electrode can be cited. From the viewpoint of further improving the conduction reliability, the electrode is preferably a copper electrode or a gold electrode, more preferably a copper electrode.
[0192] The number of the electrodes per chip is not particularly limited, and may be 1 or more, 4 or more, 20 or less, or 10 or less.
[0193] The shape of the chip is not particularly limited, and the shape of the chip can be rectangular, triangular, or circular.
[0194] The planar area of the chip is preferably 0.04 mm 2 More preferably 0.09 mm 2 More preferably, 0.16 mm 2 Above, preferably 0.50mm 2 Below, more preferably 0.40 mm 2 Below, more preferably 0.30 mm 2 When the planar area of the chip is above the lower limit, the conductive paste can be placed on fine wiring with high precision. When the planar area of the chip is below the upper limit, the RFID inlay can maintain the conduction reliability when placed in a high temperature and high humidity environment for a long time. The conductive paste of the present invention can be suitably used for bonding relatively small chips.
[0195] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples. The present invention is not limited to the following Examples.
[0196] The following materials were prepared.
[0197] (Curing compound):
[0198] Polymerizable monomers having an alicyclic skeleton:
[0199] Isobornyl acrylate ("IBXA" manufactured by Kyoeisha Chemical Co., Ltd., molecular weight: 208)
[0200] Tricyclodecane dimethanol diacrylate ("IRR-214" manufactured by DAICEL ALLNEX, molecular weight: 304)
[0201] 1,4-Cyclohexanedimethanol monoacrylate ("CHDMMA" manufactured by MITSUBISHI CHEMICAL Co., Ltd., molecular weight: 198)
[0202] Polymerizable monomers not having an alicyclic skeleton:
[0203] Polyester urethane acrylate ("UN-353" manufactured by Negami Industries, Ltd., molecular weight (weight average molecular weight): 5000)
[0204] Polyether urethane acrylate ("UN-6306" manufactured by Negami Industries, Ltd., molecular weight (weight average molecular weight): 6600)
[0205] Trimethylolpropane triacrylate ("A-TMPT" manufactured by Shin-Nakamura Chemical Industry Co., Ltd., molecular weight: 296)
[0206] Hydroxyethyl methacrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., molecular weight: 130)
[0207] 2-Phenoxyethyl acrylate ("EBCRYL114" manufactured by DAICEL ALLNEX, molecular weight: 192)
[0208] Conductive filler:
[0209] “NIELB-005-S” manufactured by Sekisui Chemical Co., Ltd. (conductive particles comprising substrate particles and a conductive portion disposed on the surface of the substrate particles, content of nickel in 100% by weight of the conductive portion: 52% by weight, average particle size: 5 μm)
[0210] NIKKO-RICA "4SP-10" (metal particles (nickel), average particle size: 6.5 μm)
[0211] Mitsui Mining & Smelting Co., Ltd. "1300Y" (metal particles (copper), average particle size: 3.5 μm)
[0212] Curing agent:
[0213] "PERBUTYL PV" manufactured by NOF Corporation (peroxyester-based radical polymerization initiator (tert-butyl peroxybutyrate))
[0214] Inorganic fillers:
[0215] Silicon dioxide ("SSP-04M" manufactured by TOKUYAMA)
[0216] chip:
[0217] IC chip (copper electrode, NXP "UCODE7", plane area: 0.22mm 2 )
[0218] Substrate:
[0219] PET film (long strip, resin film with aluminum wiring operating frequency in the UHF band (860MHz to 920MHz), surface tension: 43mN / m)
[0220] (Example 1)
[0221] (1) Preparation of conductive paste
[0222] The materials shown in Table 1 below were mixed in the amounts shown in Table 1 below, and stirred using a planetary stirring device ("AWATORI Rentaro" manufactured by THINKY Corporation) to obtain a conductive paste (anisotropic conductive paste).
[0223] (2) Preparation of RFID Inlay
[0224] On the PET film, the obtained conductive paste is applied by a jet dispensing method to form a conductive paste layer (adhesive layer) (first configuration step). Next, on the surface of the conductive paste layer (adhesive layer) opposite to the substrate side, the IC chip is stacked in a manner such that the wiring on the surface of the PET film and the electrodes on the surface of the chip are opposite to each other (second configuration step). Then, heat pressing is performed under the conditions of an upper heating tool of 180°C, a lower heating tool of 175°C, a pressure of 2N, and a pressing time of 7 seconds to solidify the conductive paste layer (adhesive layer) and form an adhesive portion. In addition, the wiring on the surface of the PET film and the electrodes on the surface of the chip are electrically connected through the conductive filler (conductive particles) in the adhesive portion to obtain a connected structure (adhesive step). It should be noted that the first configuration step, the second configuration step, and the bonding step are performed using "DDA40000" (roll-to-roll method) manufactured by Muhlbauer. The obtained connected structure was cut into a size of 5 cm×1.5 cm using “DCL30000” manufactured by Muhlbauer, thereby obtaining 50 RFID inlays.
[0225] (Examples 2 to 10 and Comparative Examples 1 to 3)
[0226] A conductive paste and an RFID inlay were obtained in the same manner as in Example 1 except that the ingredients and amounts of the conductive paste were changed as shown in Tables 1, 3, and 5.
[0227] (evaluate)
[0228] (1) Water absorption of the cured product
[0229] The obtained conductive paste was heated at 130°C for 10 minutes to obtain a cured product (cured product before the test). The cured product was immersed in water for 2 hours under the conditions of 121°C, 100% RH and 2 atm to obtain a cured product after the test. The weight of the cured product before the test and the weight of the cured product after the test were measured to calculate the water absorption of the following cured product.
[0230] Water absorption rate of the cured product (%) = (weight of the cured product after the test - weight of the cured product before the test) × 100 / weight of the cured product before the test
[0231] (2) Storage modulus
[0232] The cured product before the test and the cured product after the test obtained by (1) were cut into a size of 10 mm in length, 1 mm to 10 mm in width, and 15 mm to 50 mm in height to prepare a measurement sample. For each measurement sample, a dynamic viscoelasticity measuring device ("RSA3" manufactured by TA Instruments) was used to measure the storage modulus of the cured product before the test and the storage modulus of the cured product after the test under the conditions of a frequency of 10 Hz, a strain of 0.1%, a temperature of 20°C to 180°C, and a heating rate of 10°C / min. In addition, the ratio (storage modulus of the cured product after the test / storage modulus of the cured product before the test) was calculated.
[0233] (3) Conductivity reliability
[0234] 50 obtained RFID inlays were placed in a dark box that blocked external radio waves, and a frequency reader ("Tagformance Pro" manufactured by Voyantic) was used to measure the peak sensitivity at 25°C in the UHF band (860MHz to 920MHz) as the initial peak sensitivity. In addition, the obtained RFID inlay was immersed in water for 30 minutes and then dried. For the immersed RFID inlay, the peak sensitivity at 25°C in the UHF band was similarly measured, and the absolute value of the difference with the initial peak sensitivity was calculated. The initial and post-immersion conduction reliability was determined based on the following criteria.
[0235] [Criteria for determining initial conduction reliability]
[0236] ○○: The initial peak sensitivity of all RFID inlays is less than -18dBm
[0237] ○: Not any of ○○ and ×
[0238] ×: The initial peak sensitivity of at least one RFID inlay is -17dBm or higher
[0239] [Criteria for determining conduction reliability after immersion]
[0240] ○○: The absolute value of the difference in peak sensitivity of all RFID inlays is less than 2 dBm
[0241] ○: Not any of ○○ and ×
[0242] ×: The absolute value of the difference in initial peak sensitivity of at least one RFID inlay is 3 dBm or more. The composition and results of the conductive paste are shown in Tables 1 to 6 below.
[0243] [Table 1]
[0244]
[0245] [Table 2]
[0246]
[0247] [Table 3]
[0248]
[0249] [Table 4]
[0250]
[0251] [Table 5]
[0252]
[0253] [Table 6]
[0254]
[0255] Explanation of symbols
[0256] 1…Conductive filler
[0257] 81…RFID Inlay
[0258] 82…Substrate with wiring on the surface
[0259] 82a…Wiring
[0260] 83…Chip with electrodes on the surface
[0261] 83a…Electrode
[0262] 84…bonding part
Claims
1. A conductive paste comprising a curable compound, a curing agent and a plurality of conductive fillers, wherein: The curable compound includes a polymerizable monomer having an alicyclic skeleton, When the cured product of the conductive paste was immersed in water for 2 hours at 121° C., 100% RH and 2 atm, the water absorption of the cured product was 2.0% or less. Water absorption rate of the cured product (%)=(weight of the cured product after the test-weight of the cured product before the test)×100 / weight of the cured product before the test.
2. The conductive paste according to claim 1, wherein The storage modulus of the cured product before the test is 0.8 GPa or more, The storage modulus of the cured product after the test was 0.5 GPa or more.
3. The conductive paste according to claim 1 or 2, wherein A ratio of the storage elastic modulus of the cured product after the test to the storage elastic modulus of the cured product before the test is 0.5 or more.
4. The conductive paste according to any one of claims 1 to 3, wherein The polymerizable monomer having an alicyclic skeleton has a (meth)acryloyl group.
5. The conductive paste according to any one of claims 1 to 4, wherein The polymerizable monomer having an alicyclic skeleton is tricyclodecane dimethanol di(meth)acrylate or isobornyl (meth)acrylate.
6. The conductive paste according to any one of claims 1 to 5, wherein The content of the polymerizable monomer having an alicyclic skeleton in 100% by weight of the curable compound is 10% by weight or more and 50% by weight or less.
7. The conductive paste according to any one of claims 1 to 6, wherein The conductive filler includes nickel.
8. The conductive paste according to any one of claims 1 to 7, which is used for obtaining an RFID inlay.
9. An RFID inlay comprising: A substrate having wiring on its surface, A chip having electrodes on its surface, and A bonding portion for bonding the substrate and the chip together. The material of the bonding portion is the conductive paste according to any one of claims 1 to 8, The wiring and the electrode are electrically connected via the conductive filler in the bonding portion.
10. A method for manufacturing an RFID inlay, comprising: A first arrangement step of arranging the conductive paste according to any one of claims 1 to 8 on a surface of a substrate having wiring on the surface; a second placement step of placing a chip having an electrode on a surface of the conductive paste opposite to the substrate side; and The bonding step is to heat and pressurize the conductive paste to form a bonding portion where the substrate and the chip are bonded together by the conductive paste, and to electrically connect the wiring and the electrode via the conductive filler in the bonding portion.
11. The method for manufacturing an RFID inlay according to claim 10, wherein: The substrate is in the shape of a long strip. In the first arrangement step, the second arrangement step, and the bonding step, the RFID inlay is manufactured by conveying the long substrate by a roll-to-roll method.
Citation Information
Patent Citations
Low temperature snap curing type material having suitable pot life
JP2006144018A
Conductive adhesive and connecting method for electronic part
JP2013124330A